Experimental Study Of R141b Flow Boiling Compact Evaporator in Organic Rankine Cycle for Waste Heat Recovery - Nurdiansyah, Candra; Prabowo, Prabowo; Abdullah, Muhammad Yunus (IPTEK Journal of Proceedings Series, 2019)
Indonesia is one of country that has plenty geothermal energy resource. Because of the significant potential, the energy can be used as a power plant. Geothermal resource with low pressure and temperature can be used in Organic Rankine Cycle (ORC) technology. ORC is one of power plant system which can use waste energy by using organic working fluid or refrigerant that is able to evaporate at low pressures and temperatures . In this research, experimental of evaporator by using the organic Rankine cycle system from the gas stove heat source.The experimental study was conducted by experimenting of evaporator Compact Heat Exchanger continuous fin type. For know typical of heat transfer, evaluation proses make three region, subcooled, evaporation and superhaet. The prediction of the Two phase change flow pattern was observed in detail against the effect of heat flux and mass velocity variations by Chen and Shah Correlation. The phase change process occurs under pressure conditions P = 5 bar where the saturation temperature is 86.9 oCFrom the calculation and analysis, the maximum rate of heat transfer is 17.345 kW at 468 kg/m2s and heat flux 83 kW/m2. The evaporation process occurs at temperatures above 95 oC. Internal tube heat transfer coefficient of two-phase convection with consideration of the highest nucleate boiling and convective boiling of the evaporator was 2443.69 W/m2K in 234 kg/m2s mass flux refrigerant. Heat Flux with 1.94 kW/m2 heaten (Chen's Methode) and from the result of analysis proposed by Shah's Methode was obtained 1624.90 W/m2K in 468 kg/m2s mass flux refrigerant and 1.94 kW/m2 heat flux. the value of convection coefficient varies to the value of heat flux, mass flux and quality vapor